Effects of Ce-Doping on the Structure and NH3-SCR Activity of Fe/Beta Catalyst. Issue 7 (July 2015) - Jun, Li; Liwei, Jia; Weiyang, Jin; Feng, Xia; Jiaming, Wang
Abstract: Fe/Beta zeolite selective catalytic reduction (SCR) catalysts supported on honeycomb ceramic were prepared by a standard water ion exchange method and evaluated in NO x conversion process. The zeolite material characters and effects of Ce-doping on the zeolite were investigated by Inductively Coupled Plasma Atomic Emission Spectrum (ICP-AES), low temperature N2 adsorption, X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM), NH3 Temperature-Programmed Desorption (NH3 -TPD) and H2 Temperature-Programmed Reduction (H2 -TPR). The results show that the Fe-Beta zeolite SCR catalysts with better zeolite structure and Ce-doping exhibit a more excellent catalytic ability on the NO x conversion temperature window, no matter for the fresh one or the one treated under hydrothermal or sulfur aged condition. It is deduced that the larger BET surface area, more uniform and smaller particles and more regular framework of zeolite as well as the unsaturated Ce 4+ on zeolite have a great effect on the promotion of NH3 -SCR performance.